CORRELATION BETWEEN TEMPERATURE OF THE MUCOUS MEMBRANE AND SECRETION OF THE HARD PALATE MINOR SALIVARY GLANDS IN DIFFERENT TERMS OF USING THE FULL REMOVABLE DENTURES - Khilinich, Ye.S.; Nidzelskiy, M.Ya.; Davydenko, V.Yu.; Davydenko G.М.; Kuznetsov, V.V. (World of Medicine and Biology, 2020)
The paper considers correlation between dental structures and the condition of oral tissues, namely: changes in temperature and secretion of the minor salivary glands of the hard palate at different time periods of use of full removable laminar dentures made of acrylic resin. The findings of the studies of temperature rates of the mucous membrane of the hard palate and the condition of secretion of the minor palatine salivary glands show the significant changes in them under the action of the full removable denture base, made of acrylic resin. The increase in temperature beneath the denture base contributes to the phenomena of “greenhouse effect”, which causes inflammatory processes of various kinds in the tissues of the prosthetic bed, which can further cause destructive and atrophic changes in the minor salivary glands of the hard palate, which in turn leads to their impaired secretion – hyposalivation. Obviously, there is a directly proportional relationship between the change in temperature of the mucous membrane of the prosthetic bed beneath the denture base and the condition of secretion of the minor palatine salivary glands at different times of use of the full removable dentures.